STATISTICAL ASSESSMENT OF SUSTAINABLE ECONOMIC DEVELOPMENT OF KHOREZM REGION - Z. X.Toshmatov (Galaxy International Interdisciplinary Research Journal, 2022)
In this article, a descriptive analysis of the system of statistical indicators that characterize the sustainable development of the regions, econometric models of the transformation of the sustainable development of the regions into the standard of living of the population, statistical evaluation of the sustainable development of the Khorezm region's economy are studied.